Pengaruh Bermain Air dan Keterampilan Motorik terhadap Pengendalian Kecemasan dalam Pembelajaran Renang - Mega Sriwahyuni; Yudy Hendrayana; Sucipto Sucipto (Jurnal Sporta Saintika, 2026)
This study aims to systematically examine the influence of water play models and aquatic-based learning on motor skill development and anxiety control in elementary school swimming education. The study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Articles published between 2021 and 2024 were retrieved from ScienceDirect, Springer, and PubMed using keywords related to water play models, aquatic interventions, motor skills, and anxiety regulation. Of the 30 articles initially identified, five high-quality studies (Q1–Q2 indexed journals) met the inclusion criteria and were analyzed using a thematic synthesis approach. The findings indicate that structured water play activities significantly improve fundamental motor skills, including balance, coordination, and body control, while simultaneously reducing anxiety levels and physiological stress responses in children. Three main patterns were identified: (1) enhancement of motor proficiency through task-oriented aquatic activities, (2) reduction of anxiety through enjoyable and low-pressure water learning environments, and (3) the role of play-based aquatic pedagogy in fostering inclusive and student-centered physical education settings. This review confirms that water play models function not only as strategies for improving motor competence but also as effective approaches to supporting children’s emotional regulation.